(untitled) (Al-Adab Journal, 2019)
The harmony between the various segments of society, the consolidation of the concept of national authority, and the embodiment of the principle of identity, are the basic determinants on which the building of the national state is based on the principle of citizenship. These foundations were necessary to be observed during the period of state formation in modern Iraq, but the interference of external actors prevented this from being achieved, thanks to their influence on the nature of the ruling system in Iraq (monarchies, sheikhs, sects, ethnicities, and tribal leaders) as all this agendas and calculations were taken into account. On the one hand, partisan and clan ideological conflicts on the other hand made it difficult to complete the construction of their frameworks, at the expense of the Iraqi state. The period of Abdul Karim Qasim’s rule greatly affected the political, military, economic and social scene of Iraq, as it represented an important juncture in its contemporary history, considering that this country is of vital importance in the Middle East region despite its recent era of independence and the fragility of its political system. In this research paper, we will try to address the most important political developments in Iraq during the rule of Abd al-Karim Qasim and the relationship of power during his reign with political and societal organizations. The problem of the intervention revolved around the extent to which his period of rule 1958-1963 influenced political life in Iraq, and was it the result of the political situation or his desire to reach power?